Reduced risk of cancer among low‐dose aspirin users: Data from French health care databases. Issue 9 (23rd July 2019) - Ajrouche, Aya; De Rycke, Yann; Dalichampt, Marie; Messika Zeitoun, David; Hulot, Jean‐Sebastien; Estellat, Candice; Tubach, Florence
Abstract: Purpose: The effect of chronic use of low‐dose aspirin (LDA) on overall cancer is still unclear owing to many controversial results and methodological limitations of studies. This study aimed to assess the effect of LDA use on overall cancer incidence among the French population. Methods: We conducted a 10‐year historical cohort study using the permanent sample of the French national health care databases: the Système National des Données de Santé (SNDS). We used data for 111 025 individuals aged 50 to 80 years at study entry (January 1, 2006) without prevalent cancer or LDA use. Individuals were followed until the earliest of cancer incidence, death from any cause, exit from the database, or end of the study on December 31, 2015. We estimated the effect of LDA on cancer incidence by using a dynamic model to account for the competing risk of death in the presence of time‐dependent exposure and risk factors. Results: LDA use was associated with reduced 10‐year risk of cancer (subdistribution hazard ratio [SHR] 0.81 [95% CI 0.77‐0.86]). The SHRs were 0.88 [0.82‐0.94] for men and 0.93 [0.85‐1.02] for women. Moreover, each additional year of LDA use was associated with reduced 10‐year risk of cancer (SHR 0.93 [0.92‐0.95]). LDA use was also associated with reduced 10‐year risk of death (SHR 0.86 [0.82‐0.91]). Conclusions: This is the first population‐based study to demonstrate a protective effect of LDA on overall cancer incidence and to account for the main methodological issues of previous observational studies.